Implementation and operation of a clinical information system in a therapeutic community - Saucedo, Gary; Friso, Fabio; Politi, Matteo (Revista Científica de Sistemas e Informática, 2021)
Information and communication technologies (ICT) have a growing impact in the health sector, are oriented towards the optimization of processes and their application covers fields such as psychotherapy and occupational therapy. The objective of this article is to describe the information system Plus, an initiative of the therapeutic community Takiwasi that arises from the need to establish a platform for the collection, storage and management of the different clinical processes and data that are generated within the institution throughout the treatment of drug-addict patients. The peculiarity of this system is closely linked to the uniqueness of the treatment protocol for addiction proposed in Takiwasi, where the practices of traditional Amazonian medicine are associated with modern psychotherapy, classic biomedical follow-up and other therapeutic spaces belonging to alternative and complementary medicine. The different modules by which the system is constituted are presented, as well as the information registration process. This ICT represents a fundamental tool to promote research on the therapeutic applications of traditional medicine and serves as key feedback for therapeutic interventions.